3 - The Challenges and Possibilities of New Media in African Scholarship: The Case of Safundi and U.S.-South African Comparative Studies - Christopher J. Lee,; Andrew Offenburger, (Africa Media Review, 2007)
With the publication of several seminal works in the 1980s and 1990s, George Fredrickson and others informally established the field of U.S. and South African comparative studies. The commercial and critical success of these works catapulted such comparative scholarship from the footnotes of research papers to a subject actively engaged in academic circles. For the past five years, the journal Safundi: The Journal of South African and American Comparative Studies—and its online community—has sought to develop the comparative field beyond the foundation provided by Fredrickson etal by harnessing the strengths of electronic publishing. The result has not only been a deepening of knowledge and broadening of disciplinary focus, but the website and its related resources have improved knowledge dissemination and community building amongst comparative scholars in and out of Africa. Using the development of Safundi as a case study, Andrew Offenburger and Christopher Lee discuss the possibilities, challenges, and ultimate importance of electronic publishing to Africa-related scholarship. The authors trace the development of Safundi from its debut in 1999 to its five-year anniversary in June 2004, a period of time when Safundi expanded from an academic journal to an entire comparative community of two thousand members worldwide, with an editorial board of scholars from Africa and elsewhere, and with varied online resources: The Safundi Member Research Newsletter, the Online Member Database, the Comparative Bibliographic Database, and a compendium of comparative syllabi. Issues of information access, online databases, electronic journal publishing, electronic resource sharing, and community building, among others, are addressed both qualitatively and quantitatively, as revealed by the Safundi example. The authors also set this case study within a historical context and suggest ways that the journal—and Africa-related electronic scholarship, more broadly—may further develop in the immediate future.